Can lncRNAs be indicators for the diagnosis of early onset or acute schizophrenia and distinguish major depressive disorder and generalized anxiety disorder?—A cross validation analysis. Issue 4 (28th March 2017) - Cui, Xuelian; Niu, Wei; Kong, Lingming; He, Mingjun; Jiang, Kunhong; Chen, Shengdong; Zhong, Aifang; Li, Wanshuai; Lu, Jim; Zhang, Liyi
Abstract : Depression and anxiety are apparent symptoms in the early onset or acute phase of schizophrenia (SZ), which complicate timely diagnosis and treatment. It is imperative to seek an indicator to distinguish schizophrenia from depressive and anxiety disorders. Using lncRNA microarray profiling and RT‐PCR, three up‐regulated lncRNAs in SZ, six down‐regulated lncRNAs in major depressive disorder (MDD), and three up‐regulated lncRNAs in generalized anxiety disorder (GAD) had been identified as potential biomarkers. All the lncRNAs were, then, cross‐validated in 40 SZ patients, 40 MDD patients, 40 GAD patients, and 40 normal controls. Compared with controls, three up‐regulated SZ lncRNAs had a significantly down‐regulated expression in GAD, and no remarkable differences existed between MDD and the controls. Additionally, the six down‐regulated MDD lncRNAs were expressed in an opposite fashion in SZ, and the expression of the three up‐regulated GAD lncRNAs were significantly different between SZ and GAD. These results indicate that the expression patterns of the three up‐regulated SZ lncRNAs could not be completely replicated in MDD and GAD, and vice versa. Thus, these three SZ lncRNAs seem to be established as potential indicators for diagnosis of schizophrenia and distinguishing it from MDD and GAD. © 2017 Wiley Periodicals, Inc.